Smart specialization policies: innovative performance models from European regions - Lopes, João (2019)
This research seeks to identify the factors that best explain the performance of regional innovation in Europe, in the era of smart specialization. Data were collected from the Regional Innovation Scoreboard 2016 and a quantitative methodology was followed using linear regressions as statistical methods. The results allowed us to reach four explanatory models of performance innovation for Innovative Regions Leader, Strong, Moderate and Modest. Some policies have also been suggested as possible regional innovation measures that can help policy makers to clarify and improve the innovation performance of these regions.